Energy release sites in magetic fields containing single or multiple nulls - Galsgaard, K.; Reddy, R.V.; Rickard, G.J. (My University, 1997)
An ongoing debate is how magnetic energy is released in solar flares, which type of magnetic instabilities are responsible for triggering the energy release, and which magnetic topologies are most likely to host the instabilities. In this connection magnetic reconnection has been a general ingredient, with most of the previous work focussing on 2D reconnection. A natural extension to this is to investigate reconnection in 3D topologies, in particular the behaviour of magnetic nulls and the magnetic topology associated with them. This paper investigates the difference in dynamical behaviour of a numerical domain that either contains a double null-point pair connected by a separator or only a fraction of the separator defined by the null-points. The experiments show that nulls can either accumulate current individually, or act together to produce a singular current collapse along the separator. The implication of these results for the interpretation of coronal data is discussed.
Keywords: Magnetogram; Magnetic field; Coronal data; Magnetic topologies